GELASTIC SEIZURES: NO LAUGHING MATTER. Issue 10 (9th September 2014) - Appleton, Jason; Hayton, Tom; McCorry, Doug
Abstract : Introduction: Gelastic seizures are usually the first manifestation of hypothalamic hamartomas. Progression to intractable epilepsy with multiple seizure types occurs. Typical temporal lobe seizures with corresponding temporal lobe electrographic changes occur and represent spread of electrical activity from the hypothalamic hamartoma to the cortex. Such patients have undergone temporal lobectomy with no clinical improvement. The only curative management is removal of the hamartoma. Case: A 30 year old lady with gelastic seizures since age 12 progressed to have simple and complex partial seizures that were drug refractory. She had multiple MRIs reported as normal and underwent vagal nerve stimulator insertion in 2007 with limited benefit. Video telemetry, positron emission tomography-computed tomography (PET-CT) and subdural electrode recording were supportive of the right temporal lobe being the source. She underwent right temporal lobectomy with hippocampectomy with hippocampal sclerosis on histology. She re-attended six weeks post-operatively with seizure recurrence. Repeat MRI revealed a right hypothalamic hamartoma, which on re-review was present on her 2010 MRI. Her seizure frequency continues to increase and she is awaiting consideration of further surgical intervention. Conclusion: Gelastic seizures although rare should prompt investigation for a hypothalamic hamartoma. Surgical intervention is the key to curative management.